What Matters to Academic Performance: A Brief Review of Literature (International Journal of Scientific Research and Management (IJSRM), 2025)
This brief review of literature is conducted to highlight what matters to academic performance of the student in general. The review covered numerous researches conducted on factors and determinants of academic achievement with wide range in terms of context and condition but the main aim of this review was gaining insight of variables related to academic achievement of the student and due to the multifaceted factors affecting the academic performance the reviewed literature concentrated on four dimensions which are; social and demographic factors, institutional factors, instructional factors and student characteristics. The multitude factors affecting the academic performance of the students portrayed in this review might not limited to the four dimensions illustrated in this article but the selected studies for this review have highlighted the main factors that matters to academic performance of the student even though there is no consensus upon the exact factors that have decisive weight in this regard. However, the researches related to student characteristics and traits especially academic background and learning skills have shown more impact on academic performance than other factors related to the school facilities and instructional methods. Even so, the impact of school environment such as resources available and facilities provided as well as the role of the teachers’ teaching techniques and methods are undeniable.